Assessing Future Water Resources : The Influence of Climate Change, Population Growth and Land Use Change in the Lower Cape Fear Basin, North Carolina - Griffin, Michael T. (East Carolina University, 2011)
With the possibility of future fresh water shortages increasing, a methodology for predicting future water availability conditions is needed. This research outlines a methodology to estimate these conditions based on the influence of climate change, land use change, and population growth. The method is based on the USGS Thornthwaite monthly water balance model and can incorporate estimates of climate change and land use change parameters to assess future water resources based on predicted monthly fluxes of the water balance. The methodology is demonstrated by analyzing watersheds in the lower Cape Fear River basin located in southeast North Carolina.   The southern United States is a rapidly growing region. Trends present in the population data are used to produce future estimates of population for the basin. Precipitation and temperature estimates based on Intergovernmental Panel on Climate Change (IPCC) predictions and current climatology are inputs to the model. Projected increases in impervious surface cover due to population growth and urbanization are incorporated through the model runoff factor. Water stress indicators are used to categorize the region as water rich, water stressed, or water scarce. Scenarios incorporating regional predictions of climate change indicate a decrease in summer soil moisture minima and increases in summer water deficits. The impact of impervious surface cover enhances these deficits. Ensemble runs indicate a shift toward water stress in the lower Cape Fear River basin in the future, due to a warming climate as well as increased demand. While climate change has a significant impact on water resources in the region, population growth has the most substantial impact as it not only impacts demand, but climate and land use as well.
Keywords: Physical geography; Climate changes; Water resources management; Geography; Impervious surface; Water balance; Water resources; Water stress; Water-supply--North Carolina; Cape Fear River Watershed (N.C.); Climatic changes--Environmental aspects--North Carolina; Population--Environmental aspects; Land use--North Carolina; Watersheds--North Carolina